2016
DOI: 10.1142/s0218301316500592
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of ground and excited states of pseudoscalar and vector charmonium and bottomonium

Abstract: In this work we calculate the mass spectrum, weak decay constants, two photon decay widths, and two gluon decay widths of ground (1S), and radially excited (2S, 3S,...) states of pseudoscalar charmoniuum and bottomonium such as η c and η b , as well as the mass spectrum and leptonic decay constants of ground state (1S), excited (2S, 1D, 3S, 2D, 4S,...,5D) states of vector charmonium and bottomonium such as J/ψ, and Υ, using the formulation of Bethe-Salpeter equation under covariant Instantaneous Ansatz (CIA). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
97
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(100 citation statements)
references
References 52 publications
2
97
1
Order By: Relevance
“…However, the price one pays in this approach is to solve a coupled set of Salpeter equations for both pseudoscalar and vector quarkonia. However, in [21], we explicitly showed that these coupled Salpeter equations can indeed get decoupled in the heavy-quark approximation, leading to mass spectral equations with analytical solutions for both masses, as well as eigenfunctions for all the ground and excited states of pseudoscalar and vector and systems 2 Advances in High Energy Physics in an approximate harmonic oscillator basis. These analytical forms of eigenfunctions for ground and excited states so obtained were used to evaluate the transition amplitudes for different processes in [21].…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…However, the price one pays in this approach is to solve a coupled set of Salpeter equations for both pseudoscalar and vector quarkonia. However, in [21], we explicitly showed that these coupled Salpeter equations can indeed get decoupled in the heavy-quark approximation, leading to mass spectral equations with analytical solutions for both masses, as well as eigenfunctions for all the ground and excited states of pseudoscalar and vector and systems 2 Advances in High Energy Physics in an approximate harmonic oscillator basis. These analytical forms of eigenfunctions for ground and excited states so obtained were used to evaluate the transition amplitudes for different processes in [21].…”
Section: Introductionmentioning
confidence: 96%
“…However, in [21], we explicitly showed that these coupled Salpeter equations can indeed get decoupled in the heavy-quark approximation, leading to mass spectral equations with analytical solutions for both masses, as well as eigenfunctions for all the ground and excited states of pseudoscalar and vector and systems 2 Advances in High Energy Physics in an approximate harmonic oscillator basis. These analytical forms of eigenfunctions for ground and excited states so obtained were used to evaluate the transition amplitudes for different processes in [21]. Thus, in [21], we had calculated the mass spectrum, weak decay constants, two-photon decay widths and two-gluon decay widths of ground (1 ) and radially excited (2 , 3 , .…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations